PENGARUH MODEL THINK PAIR SHARE BERBANTUAN MEDIA FLIPSNACK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD - Listiana Sari, Eva; Ismiyanti, Yulina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low reading comprehension ability of elementary school students, especially in understanding the content of reading and finding important information. This study aims to determine the effect of the Think Pair Share learning model assisted by Flipsnack media on the reading comprehension ability of fourth grade students at SD Negeri Gebangsari 03. This study uses a quantitative approach with an experimental type and One Group Pretest–Posttest design. The research subjects were 28 students. Data collection was carried out through pretest and posttest tests that had been tested for validity and reliability. Data analysis used normality tests and paired sample t-tests. The results showed an increase in students' average scores after treatment, and a significance value of less than 0.05. Thus, the Think Pair Share model assisted by Flipsnack media is effective in improving elementary school students' reading comprehension abilities.